2018
DOI: 10.1016/j.avsg.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes after Ruptured Abdominal Aortic Aneurysms Repair: Is Endovascular Aortic Repair the Best Choice? A Single-Center Experience

Abstract: EVAR does not independently reduce 1-year mortality in comparison with OSR in Hd stable patients. Urgent EVAR for rAAAs in unstable patients can be limited by logistical problems. It follows that patients selected for OSR have a more complex aortic anatomy and worse Hd status than those submitted to rEVAR. rEVAR burdened by a higher incidence of procedure-related complications than OSR. Reconfiguration of acute aortic services and establishment of standardized institutional protocols might be advisable for imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…The 1-year mortality for eEVAR has ranged between 60% 15 and 34%. 16,20 A single large study reported 50% mortality at 5 years for eEVAR, 20 and the IMPROVE trial 3-year data showed 48% mortality in the eEVAR cohort, which is comparable to the current series. Comparing this to open repair of rAAA, which had a survival rate of 46% at 3 years in the IMPROVE trial 3 and 42.9% at 5 years in a Swedish study, 21 the 38.3% survival at 5 years after eEVAR in the current analysis is comparable.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The 1-year mortality for eEVAR has ranged between 60% 15 and 34%. 16,20 A single large study reported 50% mortality at 5 years for eEVAR, 20 and the IMPROVE trial 3-year data showed 48% mortality in the eEVAR cohort, which is comparable to the current series. Comparing this to open repair of rAAA, which had a survival rate of 46% at 3 years in the IMPROVE trial 3 and 42.9% at 5 years in a Swedish study, 21 the 38.3% survival at 5 years after eEVAR in the current analysis is comparable.…”
Section: Discussionsupporting
confidence: 77%
“…A recent systematic review of studies including >100 eEVARs compared with open repair in the emergency setting identified 30-day mortality rates ranging from 17.4% 13 to 45.1%, 14 in line with 2 more recent studies reporting 30-day mortality at 36% 15 and 19.4%. 16 The low 30-day mortality in the current series may be due to patient selection. The turndown rate in our center has previously been reported as 19.6%.…”
Section: Discussionmentioning
confidence: 83%
“…Our results are comparable with other series which confirm reinterventions are common after OR AAA, especially after emergency OR. 21,22 Colonic ischaemia can be particularly difficult to diagnose and even after emergency colectomy the risk of mortality is high. 23,24 The median length of stay overall in hospital stay was 10 days, for elective repair 9 days and emergency repair 15 days.…”
Section: Discussionmentioning
confidence: 99%
“…Martinelli et al report a single institution 30-day mortality rate of 19.3%, while Veith et al report at 21.2% 30-day mortality across 13 centers, and randomized control trial data shows a 30-day mortality rate of 35.4%. 2,3,9 The slightly lower mortality in the single institution studies can possibly be explained by the fact that 100% of patients undergoing rEVAR were considered to by hemodynamically stable at the time of repair as compared with 58% undergoing open repair (P < 0.001), while in the randomized trials, these groups were more evenly matched in baseline presentation characteristics. 3,9,10 Patients with bilateral renal artery coverage had significant indicators of more complex repairs with increased contrast use, fluoroscopy time, procedural time, blood loss, and type Ia endoleak rates at case conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,9 The slightly lower mortality in the single institution studies can possibly be explained by the fact that 100% of patients undergoing rEVAR were considered to by hemodynamically stable at the time of repair as compared with 58% undergoing open repair (P < 0.001), while in the randomized trials, these groups were more evenly matched in baseline presentation characteristics. 3,9,10 Patients with bilateral renal artery coverage had significant indicators of more complex repairs with increased contrast use, fluoroscopy time, procedural time, blood loss, and type Ia endoleak rates at case conclusion. When the primary and secondary endpoints are considered, patients with bilateral renal artery coverage had significantly higher inhospital mortality rates, permanent dialysis/30-day mortality rates, and overall complication rates compared with patients with single renal or no renal artery coverage.…”
Section: Discussionmentioning
confidence: 99%